THE ROLE OF INHERITANCE TRADITIONS IN THE DEVELOPMENT OF SOCIETY - Isroilov, Bektosh Erkinovich (Oriental Journal of History, Politics and Law, 2025)
This article analyzes the social and philosophical issues of the innovative approach to the concept of succession. The harmony of tradition and innovation in the development of society, the processes of interaction between cultural heritage and advanced technologies are considered. The relationship between innovation and succession, and their impact on society and education are discussed.